2010
DOI: 10.1007/s11483-010-9158-z
|View full text |Cite
|
Sign up to set email alerts
|

LIBS-Based Detection of Antioxidant Elements in Seeds of Emblica officinalis

Abstract: The aim of the study was to determine the effect of the elements of the extract of seed from Emblica officinalis on antioxidant enzymes and osmotic fragility of erythrocytes membrane in normal as well as streptozotocininduced severely diabetic albino Wister rats. The results revealed that the untreated diabetic rats exhibited increase in oxidative stress as indicated by significantly diminished activities of free radical scavenging enzymes such as catalase (CAT) and superoxide dismutase (SOD) by 37.5% (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Some of the main constituents of leaf of O. sanctum are phenolic compounds, flavonoids, sesquiterpenes and monoterpenes, glycosides, Steroids, sterols as well as volatile and non volatile, (Fixed) oils [2,3]. It is suggested that all or some of these bioactive compounds may be responsible for hypoglycemic, antidyslipidemic and antioxidant effects of the medicinal plants [22,23]. Kelm et al [24,25] found that leaves and stems of Ocimum sanctum contains cirsilineol, cirsimaritin, isothymusin, isothymonin, apigenin, rosmarinic acid, and appreciable quantities of eugenol and all these are known to possess potent lipid lowering and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the main constituents of leaf of O. sanctum are phenolic compounds, flavonoids, sesquiterpenes and monoterpenes, glycosides, Steroids, sterols as well as volatile and non volatile, (Fixed) oils [2,3]. It is suggested that all or some of these bioactive compounds may be responsible for hypoglycemic, antidyslipidemic and antioxidant effects of the medicinal plants [22,23]. Kelm et al [24,25] found that leaves and stems of Ocimum sanctum contains cirsilineol, cirsimaritin, isothymusin, isothymonin, apigenin, rosmarinic acid, and appreciable quantities of eugenol and all these are known to possess potent lipid lowering and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…Mehta et al. [1] reported antioxidant elements from seeds of Emblica officinalis as detected by laser-induced breakdown spectroscopy. It was found that E. officinalis extract effected antioxidant enzymes and has the potential acted as an agent to boost the antioxidant system in the diabetic animal model.…”
Section: Introductionmentioning
confidence: 99%
“…This activity includes studies of laser ablation and properties of the laser spark, the development of methods to enhance LIBS detection capabilities, and the application of LIBS to specific analysis needs. Recently Watal's research group has been successfully applied LIBS technique for the analysis of trace elements in medicinal plants [6][7][8][9] , responsible for their specific bioactivities.…”
Section: Introductionmentioning
confidence: 99%